ANALISIS ANTESEDEN DAN DAMPAK KEBERHASILAN PENERAPAN SISTEM INFORMASI AKUNTANSI - Adli Adli (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
The purposes of this study is to test: (1) the influence of organizational commitment and knowledge manager on success of implementation accounting information system both simultaneously and partially; and (2) the influence organizational commitment; knowledge manager; and success of implementation accounting information system on companies financial performance both simultaneously and partially. The study was conducted survey method; consist of 38 BUMN in Indonesia.The sample was taken by using simple random sampling. Data collected using questionairs; and the validity and reliability of the data was tested before hypothesis testing. The data analysis for hypothesis testing using path analysis was processed by Amos 16 software. The result of this study show that: (1) the organizational commitment and knowledge manager; have a effect on success of implementation accounting information system both simultaneously and partially; and (2) the organizational commitment; knowledge manager; and success of implementation accounting information system; have aeffect on companies financial performance both simultaneously and partially.